The role of institutions in a regional innovation system and their impact on the innovation performance of organizations within the quadruple helix. - Ortega, Ana M. (Pontificia Universidad Católica del Perú, 2019)
Among the critical issues facing policy and decision makers is how to improve the regional innovation systems (RISs), as such improvement enhances the development of organizational innovative capacities, encourages innovation performance (IP), and consequently helps achieve sustainable economic development. Results of the present study allowed the construction of the institutional map of an RIS, for understanding the role of formal and informal institutions that compose the institutional framework, which enable or hinder the IP within the organizations of the quadruple helix. The RIS of Medellin was used as an instrumental case study, and the research was conducted using a qualitative, cross-sectional design, semi-structured interviews as data collection method and thematic analysis as data processing method. Research findings remark the importance of innovation supportive culture, as the main informal institution affecting the IP, as well as the crucial role of the investment, incubation and acceleration of innovation projects, through formal institutional mechanisms enabled by private and public actors. Collaboration and interaction are the rationale behind the existence of an RIS; reason why when analyzing the institutions of an RIS it is logical to find that many of them are related to these particular factors. Findings also suggest that informal institutions exert a greater influence over the IP of organizations in an RIS, than formal ones, but both types of institutions are very important, and should be complementary.
Keywords: Mercadeo; Investigación cuantitativa; Innovación; https://purl.org/pe-repo/ocde/ford#5.02.04